2019
DOI: 10.1177/2048872619870035
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of microcirculatory perfusion versus macrocirculatory perfusion in cardiogenic shock: a CULPRIT-SHOCK substudy

Abstract: Background: After early revascularisation, restoration of macrocirculatory perfusion parameters is the primary objective in the management of cardiogenic shock complicated acute myocardial infarction. Nevertheless, vital organ perfusion may be compromised at the systemic microcirculatory level, even in patients with preserved macrohaemodynamics. Microvascular perfusion was shown to have independent prognostic value for early mortality. The present study aims to compare the prognostic value of microcirculatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Our results go in line with previous investigations which highlighted the important role of the microcirculation in critical ill patients independently of global hemodynamics, 16,21,22 e.g., in septic or cardiogenic shock.…”
Section: Discussionsupporting
confidence: 93%
“…Our results go in line with previous investigations which highlighted the important role of the microcirculation in critical ill patients independently of global hemodynamics, 16,21,22 e.g., in septic or cardiogenic shock.…”
Section: Discussionsupporting
confidence: 93%
“…Microcirculatory impairment has been associated with organ injury in patients with hemorrhagic, cardiogenic, and septic shock. [47][48][49] The authors observed a progressive decline in PVD that was associated with an increased early SOFA score as well as postoperative lactate levels. Patients with the lowest PVD had both high lactate levels and increased SOFA scores.…”
Section: -26mentioning
confidence: 96%
“…A substudy of the culprit lesion-only percutaneous coronary intervention versus multivessel percutaneous coronary intervention in cardiogenic shock (CULPRIT-SHOCK) trial, used this method for assessing the impact of microcirculatory dysfunction on clinical outcome. 9 Whereas there was no significant association with macrocirculatory hemodynamic parameters, there was a significant association between microcirculatory perfusion parameters and the combined clinical endpoint of all-cause death and renal replacement therapy at 30 days follow-up. The observed incoherence between macro- and microcirculatory perfusion parameters, suggests that clinical monitoring of tissue perfusion may be more crucial than arterial blood pressure in the management of cardiogenic shock.…”
mentioning
confidence: 84%